Calculus with Applications (10th Edition)

Published by Pearson
ISBN 10: 0321749006
ISBN 13: 978-0-32174-900-0

Chapter R - Algebra Reference - R.4 Equations - R.4 Exercises - Page R-16: 36


This equation has no solution.

Work Step by Step

$\dfrac{2}{x^{2}-2x-3}+\dfrac{5}{x^{2}-x-6}=\dfrac{1}{x^{2}+3x+2}$ Factor all three rational expressions completely: $\dfrac{2}{(x-3)(x+1)}+\dfrac{5}{(x-3)(x+2)}=\dfrac{1}{(x+2)(x+1)}$ Multiply the whole equation by $(x-3)(x+1)(x+2)$: $(x-3)(x+1)(x+2)\Big[\dfrac{2}{(x-3)(x+1)}+\dfrac{5}{(x-3)(x+2)}=\dfrac{1}{(x+2)(x+1)}\Big]$ $2(x+2)+5(x+1)=x-3$ $2x+4+5x+5=x-3$ Take all terms to the left side and simplify: $2x+4+5x+5-x+3=0$ $6x+12=0$ Take $12$ to the right side: $6x=-12$ Take $6$ to divide the right side: $x=-\dfrac{12}{6}$ $x=-2$ The original equation is undefined for $x=-2$, so this equation has no solution.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.